2007
DOI: 10.1093/annonc/mdm088
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes with concurrent carboplatin, paclitaxel and radiation therapy for locally advanced, inoperable head and neck cancer

Abstract: Treatment with concurrent carboplatin, paclitaxel and radiation is safe and offers curative potential for poor prognosis patients with locally advanced SCCHN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 18 publications
1
33
2
Order By: Relevance
“…Examination of CTAB-treated wild-type [p53(ϩ/ϩ)] and mutant [p53(Ϫ/Ϫ)] colon cancer HCT116 cells (Bunz et al, 1998) demonstrated very similar sensitivity (data not shown), suggesting that CTAB-mediated toxicity is independent of p53 status, thereby increasing the potential applicability of CTAB to many different human cancers. Moreover, its favorable toxicity profile, ability to induce apoptosis in cancer cells at much lower concentrations than its antimicrobial application (Pang and Willis, 1997), and capacity to delay tumor growth in FaDu xenograft models comparable with paclitaxel (Davis et al, 2002), a commonly used chemotherapeutic agent in the clinical management of HNC patients (Agarwala et al, 2007), all suggest that optimizing the bioavailability and pharmacokinetics of CTAB could provide an exciting opportunity for the development of a highly effective drug candidate, capable of exploiting the metabolic aberrations of human head and neck cancers.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Examination of CTAB-treated wild-type [p53(ϩ/ϩ)] and mutant [p53(Ϫ/Ϫ)] colon cancer HCT116 cells (Bunz et al, 1998) demonstrated very similar sensitivity (data not shown), suggesting that CTAB-mediated toxicity is independent of p53 status, thereby increasing the potential applicability of CTAB to many different human cancers. Moreover, its favorable toxicity profile, ability to induce apoptosis in cancer cells at much lower concentrations than its antimicrobial application (Pang and Willis, 1997), and capacity to delay tumor growth in FaDu xenograft models comparable with paclitaxel (Davis et al, 2002), a commonly used chemotherapeutic agent in the clinical management of HNC patients (Agarwala et al, 2007), all suggest that optimizing the bioavailability and pharmacokinetics of CTAB could provide an exciting opportunity for the development of a highly effective drug candidate, capable of exploiting the metabolic aberrations of human head and neck cancers.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Paclitaxel -representative of the second generation chemotherapy -has been used in SCCHN single-agent [7,14] or platinum-based radiochemotherapy protocols [2,6,8,15,22,25]. Current treatment strategies often use hyperfractionated or hyperfractionated-accelerated radiotherapy protocols to enhance efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously reported that 8% to 20% of long-term survivors may become G-tube dependent. 11,12,[17][18][19] Higher doses of radiation therapy have been associated with higher rates of long-term enteral feeding. 17,20 Our group previously reported that there was no association between mean total radiation dose and G-tube dependence 6 months post-CRT.…”
mentioning
confidence: 99%